Evidence for DNA methylation mediating genetic liability to non-syndromic cleft lip/palate. (14th January 2019) - Howe, Laurence J; Richardson, Tom G; Arathimos, Ryan; Alvizi, Lucas; Passos-Bueno, Maria R; Stanier, Philip; Nohr, Ellen; Ludwig, Kerstin U; Mangold, Elisabeth; Knapp, Michael; Stergiakouli, Evie; Pourcain, Beate St; et al.
Aim: To determine if nonsyndromic cleft lip with or without cleft palate (nsCL/P) genetic risk variants influence liability to nsCL/P through gene regulation pathways, such as those involving DNA methylation.Materials & methods: nsCL/P genetic summary data and methylation data from four studies were used in conjunction with Mendelian randomization and joint likelihood mapping to investigate potential mediation of nsCL/P genetic variants.Results & conclusion: Evidence was found at VAX1 (10q25.3), LOC146880 (17q23.3) and NTN1 (17p13.1), that liability to nsCL/P and variation in DNA methylation might be driven by the same genetic variant, suggesting that genetic variation at these loci may increase liability to nsCL/P by influencing DNA methylation. Follow-up analyses using different tissues and gene expression data provided further insight into possible biological mechanisms.